Zearalenone (ZEN) and Its Metabolite Levels in Tissues of Wild Boar (Sus scrofa) from Southern Italy: A Pilot Study - Consiglia Longobardi; Sara Damiano; Gianmarco Ferrara; Serena Montagnaro; Valentina Meucci; Luigi Intorre; Samanta Bacci; Luigi Esposito; Nadia Piscopo; Antonio Rubino; Antonio Raffaele; Salvatore Florio; et al. (Toxins, 2023)
Zearalenone (ZEN) is a non-steroidal estrogenic mycotoxin produced by the fungi of the Fusarium genera, and is a contaminant of cereals and plant products. ZEN and its metabolites are considered endocrine disruptors, and could have various toxic effects on animals and humans. In recent years, there has been a significant demographic increase in wild boar (Sus scrofa) in many mountainous and hilly areas of Italy, including the Campania region, mainly due to global climate change. The wild boar can be defined as a generalist and omnivorous species capable of varying its diet; therefore, it can play a role as an environmental bioindicator towards contaminants such as mycotoxins. This study was conducted to evaluate, for the first time, the concentrations of ZEN and its metabolites in the liver, kidney, and muscle of 82 wild boars shot in their habitat by hunters with hunting permits in different localities of Avellino province (Campania region, Southern Italy) from 2021 to 2022. The samples were collected and analyzed with an SPE clean-up and high-pressure liquid chromatography method with fluorescence detection. The results indicated that ZEN and α-Zearalenol were present in most of the samples, suggesting that a plan to monitor these mycoestrogens is essential to achieve the goals of “One Health”.